2001
DOI: 10.1177/0265407501181002
|View full text |Cite
|
Sign up to set email alerts
|

Friendship Patterns among African American, Asian American, and Latino Adolescents from Low-Income Families

Abstract: Using quantitative and qualitative methods, the present study sought to explore: the patterns or types of closest, same-sex friendships among ethnic minority, low-income adolescents; the psychological and familial correlates of these patterns; and the adolescents' subjective experiences of each type of closest, same-sex friendships. Two hundred and thirteen African American, Latino, and Asian American high school students participated in the study. Results of cluster analyses suggested four types of closest, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 29 publications
9
51
0
Order By: Relevance
“…Results furthermore showed that boys were found more often in the disengaged friendship type than girls. This confirms prior results concerning perceptions of friendship quality to typify adolescents in disengaged friendships (Way et al 2001), and is consistent with findings showing that boys perceive lower friendship quality than girls (e.g., Brendgen et al 2001). Boys may value multiple relationships in peer groups more than girls (Urberg et al 1995) and may therefore be found more in adolescents in disengaged friendships than girls.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Results furthermore showed that boys were found more often in the disengaged friendship type than girls. This confirms prior results concerning perceptions of friendship quality to typify adolescents in disengaged friendships (Way et al 2001), and is consistent with findings showing that boys perceive lower friendship quality than girls (e.g., Brendgen et al 2001). Boys may value multiple relationships in peer groups more than girls (Urberg et al 1995) and may therefore be found more in adolescents in disengaged friendships than girls.…”
Section: Discussionsupporting
confidence: 91%
“…Adolescents in disengaged friendships concurrently reported higher levels of depressive symptoms than adolescents in interdependent friendships (Way et al 2001). Furthermore, high commitment and high balanced relatedness can be viewed as two indicators for high friendship quality, and cross-sectional (Kiesner et al 2003) and over-time (Prinstein et al 2005a;Stice et al 2004) associations between low perceived friendship quality and depression in adolescence have been shown.…”
Section: Friendship Types and Adolescent Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sample, MexicanAmerican adolescents spent considerable time with peers, and time with peers was linked to adolescents' cultural orientations. These findings are consistent with other work that documents the significance of friendships for Latino youth (e.g., Phinney, Romero, Nava, & Huang, 2001;Stanton-Salazar & Spina, 2005;Suárez-Orozco & Suárez-Orozco, 1995;Way et al, 2001), and suggest that examinations of peer influences on acculturation and enculturation merit future study. Because our data are cross-sectional, we were unable to draw conclusions about direction of effect: Adolescents with stronger orientations toward Mexican culture may choose to spend time in the company of Mexican peers or the other way around.…”
Section: Adolescents' Peer Involvement Parents' Cultural Orientationsupporting
confidence: 90%